THE EFFECT OF LEARNING MODELS AND INDONESIAN LANGUAGE PROFICIENCY, ON THE ABILITY TO WRITE PROCEDURAL TEXTS - Aceng Joyo; Sudarwan Danim; Didi Yulistio; S Susetyo (Erudio Journal of Educational Innovation, 2019)
The purpose of this study was to determine the effect of learning models and Indonesian language proficiency, on the ability to write procedure texts in Seluma Vocational High School students. The method used in this study is the experimental method. The data in this study were collected using test techniques, namely the writing test and the objective ability test for writing text procedures. The results showed that there was an influence between the interaction of learning models and Indonesian language proficiency on the ability to write procedure texts in class XI Vocational High School students in Seluma. The conclusion in this study is that the learning model and Indonesian language proficiency significantly influence the ability to write procedure texts of class XI students at Seluma State Vocational School.